Gastrointestinal symptoms as extrapulmonary manifestations in patients with COVID-19. A narrative review - Sánchez-Toro, Vivian (2021)
Background:SARS-CoV-2 infection mainly affects the respiratory system; but, multiple extrapulmonary manifestations have also been observed in various systems and organs. The epithelial cells of the digestive tract and hepatobiliary tree express ECA2 and TMPRSS2 necessary for viral entry, on the other hand, viral RNAhas been detected in stool samples, even after having become negative inrespiratorysamples.Thepresenceofclinicaldigestive manifestations is associated with a higher viral load and can sometimes be the only manifestations of COVID-19, even in the absence of respiratory symptoms. The most common symptoms are anorexia and diarrhea, nausea, vomiting, and abdominal pain, the latter being characteristic of seriously ill patients. Gastrointestinal bleeding, hemorrhagic colitis, or acute hepatitis are very rare. In a patient with gastrointestinal manifestations, COVID-19 should be considered within the differential diagnosis.